Cost minimization of a WWTP using an augmented lagrangian pattern search based solver - Espírito Santo, I. A. C. P. (2007)
This paper describes a derivative-free method that aims to solve an optimization problem arising from the mathematical formulation of an activated sludge system in which the objective is to minimize the investment and operation costs. The method relies on an augmented Lagrangian technique that uses a pattern search for solving bound constrained subproblems.